2021
DOI: 10.1111/are.15576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish meal replacement with low‐gossypol cottonseed meal on the intestinal barrier of juvenile golden pompano ( Trachinotus ovatus )

Abstract: The effects of replacing fish meal (FM) with low-gossypol cottonseed meal (LCSM) on the intestinal barrier in different segments (PI, proximal intestine; MI, middle intestine; DI, distal intestine) were studied in juvenile golden pompano (Trachinotus ovatus) using 6-week feeding trials. FM of 0% (diet_1), 20% (diet_2), 40% (diet_3) and 60% (diet_4) was replaced by LCSM. The FM-based diet (diet_1) containing 25% FM was used as control group. The intestinal morphology, mRNA expression of tight junctionrelated ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Shen et al discovered that dietary FM could be reduced to 13.60% with cottonseed protein concentrate without affecting the weight gain rate [28]. However, Fu et al found that the replacement of more than 20% of FM in the diet by low-gossypol cottonseed meal resulted in impaired intestinal barrier function in golden pompano [29]. Similarly, Qin et al found that the use of cottonseed meal could only reduce the feed FM content to 20% without affecting the growth of golden pompano [30] and that the fish muscle nutritive deposition was negatively affected when the feed FM was below 15% [31].…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al discovered that dietary FM could be reduced to 13.60% with cottonseed protein concentrate without affecting the weight gain rate [28]. However, Fu et al found that the replacement of more than 20% of FM in the diet by low-gossypol cottonseed meal resulted in impaired intestinal barrier function in golden pompano [29]. Similarly, Qin et al found that the use of cottonseed meal could only reduce the feed FM content to 20% without affecting the growth of golden pompano [30] and that the fish muscle nutritive deposition was negatively affected when the feed FM was below 15% [31].…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to promote the sustainable growth of aquaculture involves utilizing plant-derived byproducts to replace fishmeal. Cottonseed meal (CSM), a byproduct of cottonseed oil extraction, is widely used in aquatic feed due to its abundant availability, high protein content, and relatively low cost [4][5][6][7][8]. However, it contains anti-nutritional components that can be detrimental to animal health and performance if not appropriately managed, including free gossypol (FG), phytic acid, and tannins [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the search for protein sources to replace fish meal in aquafeed has become one of the highly researched topics in aquatic animal nutrition [3,4]. At present, alternative sources of fish meal for aquafeed mainly include animal protein [5,6], plant protein [7,8], and insect protein sources that have emerged in recent years [9,10]. Studies have shown that several animal and plant proteins could effectively replace fish meal in aquatic feed.…”
Section: Introductionmentioning
confidence: 99%